DNA-damage-induced degradation of EXO1 exonuclease limits DNA end resection to ensure accurate DNA repair - Tomimatsu, Nozomi (J Biol Chem, 2017)
End resection of DNA double-strand breaks (DSBs) to generate 3′-single-stranded DNA facilitates DSB repair via error-free homologous recombination (HR) while stymieing repair by the error-prone non-homologous end joining (NHEJ) pathway. Activation of DNA end resection involves phosphorylation of the 5′ to 3′ exonuclease EXO1 by the phosphoinositide 3-kinase-like kinases ATM (ataxia telangiectasia-mutated) and ATR (ATM and Rad3-related) and by the cyclin-dependent kinases 1 and 2. After activation, EXO1 must also be restrained to prevent over-resection that is known to hamper optimal HR and trigger global genomic instability. However, mechanisms by which EXO1 is restrained are still unclear. Here, we report that EXO1 is rapidly degraded by the ubiquitin-proteasome system soon after DSB induction in human cells. ATR inhibition attenuated DNA-damage-induced EXO1 degradation, indicating that ATR-mediated phosphorylation of EXO1 targets it for degradation. In accord with these results, EXO1 became resistant to degradation when its SQ motifs required for ATR-mediated phosphorylation were mutated. We show that upon the induction of DNA damage, EXO1 is ubiquitinated by a member of the Skp1-Cullin1-F-box (SCF) family of ubiquitin ligases in a phosphorylation-dependent manner. Importantly, expression of degradation-resistant EXO1 resulted in hyper-resection, which attenuated both NHEJ and HR and severely compromised DSB repair resulting in chromosomal instability. These findings indicate that the coupling of EXO1 activation with its eventual degradation is a timing mechanism that limits the extent of DNA end resection for accurate DNA repair.